Short-Term Inhibition of ADP-Induced Platelet Aggregation by Clopidogrel Ameliorates Radiation-Induced Toxicity in Rat Small Intestine - Wang, Junru; Albertson, Christopher M.; Zheng, Huaien; Fink, Louis M.; Herbert, Jean-Marc; Hauer-Jensen, Martin (Thrombosis and Haemostasis, 2002)
Endothelial dysfunction and increased platelet aggregation may be involved in the pathogenesis of normal tissue radiation toxicity. This study assessed clopidogrel, an inhibitor of ADP-induced platelet aggregation, as a modulator of intestinal radiation injury (radiation enteropathy).Rat small intestine was exposed to 21 Gy X-radiation. Clopidogrel (20 mg/kg/day) or vehicle was administered from 2 days before to 10 days after irradiation. Structural radiation injury, neutrophil infiltration, smooth muscle cell proliferation, collagen content, and TGF-β1 expression were assessed 2 weeks (early phase) and 26 weeks (delayed phase) after irradiation, using quantitative histology and immunohistochemistry, morphometry, and real-time fluorogenic probe RT-PCR.Irradiated intestine exhibited significant histopathologic injury, reduced mucosal surface area, vascular sclerosis, intestinal wall fibrosis, increased collagen content, and increased TGF-β1 expression. Clopidogrel reduced ADP-induced platelet aggregation by 93% and significantly attenuated the severity of post-radiation vascular sclerosis (p = 0.004 and p = 0.02) and the loss of mucosal surface area (p = 0.0008 and p = 0.003) at both 2 and 26 weeks. Clopidogrel also ameliorated overall histopathologic injury (p = 0.02), relative intestinal collagen content (p = 0.03), and collagen III immunoreactivity levels 2 weeks after irradiation, and caused a borderline reduction in the radiation-induced increase in extracellular matrix-associated TGF-β immunoreactivity at 26 weeks (p = 0.04). The effects of clopidogrel on steady-state TGF-β1 mRNA levels and neutrophil infiltration were not statistically significant.Short-term clopidogrel administration affords protection against early and, to a lesser extent, delayed radiation enteropathy. Modulation of platelet aggregation should be subject to further studies as a potential method to increase safety and efficacy of radiation therapy.
Keywords: Platelet aggregation; clopidogrel; radiation therapy; intestines; radiation injuries; experimental